Understanding Policing of Human Trafficking in Gauteng Province, South Africa: The Phenomena, Challenges and Effective Responses - Motseki, Morero (International Journal of Criminology and Sociology, 2022)
Human trafficking is one of the most heinous crimes perceived to be a serious and growing problem worldwide. Human trafficking is a depressing phenomenon that affects many people across the globe. This study attempts to determine the phenomena of human trafficking, and identify the existing challenges of policing this scourge and suggest possible effective responses. This study was carried out utilising a qualitative approach. Forty interviews were carried out among officials deployed in the Directorate for Priority Crime Investigation (DPCI), the South African Police Service (SAPS), the Department of Home Affairs (DHA), the Department of Social Development (DSD), the Gauteng Provincial Office, as well as with the victims regarding their views and experiences on the stakeholder’s involvement in combating and investigating human trafficking. The key findings indicated that the challenges are corruption, lack of motivation and commitment to combat human trafficking, lack of limited awareness and information about the human trafficking scourge in South Africa, the findings also indicated a lack of clear strategy and response by stakeholders to successfully investigate, prosecute and incarcerate the perpetrators of human trafficking and the findings further indicated lack of capacity, resources and training to deal with human trafficking. Based on the findings, the author provided, possible recommendations such as; the utilisation of advanced technology and use of intelligence-led policing to strengthen the work of stakeholders, advanced training and better education including improved awareness strategies; and the utilisation of social media as a tool to deal with human trafficking and strengthening of enforcement responses and reporting techniques.